Association of delirium with post-traumatic stress disorder: a systematic review and meta-analysis - Yang, Xia; Chen, Fang; Jiang, Zhixia; Xu, Nan; Zhang, Xia; Chen, Qingqing; Cao, Mingwei (Frontiers in Psychiatry, 2025)
BackgroundDelirium, a prevalent form of acute brain dysfunction, is characterized by perceptual disturbances that may lead to the formation of delusional memories. This pathological process could subsequently elevate the risk of developing posttraumatic stress disorder (PTSD). However, the findings of previous research are inconsistent, and the association has not been systematically evaluated. Therefore, this study attempts to clarify the epidemiological relationship between delirium and PTSD as well as its clinical significance through a thorough integration of the available data, aiming to provide an evidence-based foundation for the early identification of high-risk patients and the creation of focused intervention strategies.MethodsWe followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines during the literature search. Comprehensive searches were conducted in PubMed, Ovid MEDLINE, APA PsycINFO, Embase, Scopus, and CINAHL, covering all relevant literature published from each database’s inception until April 3, 2025. The search strategy combined free-text terms with controlled vocabulary (MeSH/Emtree terms) related to delirium and PTSD. This systematic review was registered with PROSPERO (CRD420251031880).ResultsA total of 11 articles were included in this study. Meta-analysis of unadjusted ORs revealed that patients with delirium exhibited a significantly higher risk of developing PTSD compared to non-delirium controls (OR = 3.31, 95% CI [2.21–4.97]). After adjusting for potential confounders, the pooled results based on adjusted ORs continued to indicate a significant association between delirium and increased PTSD risk (OR = 3.96, 95% CI [1.85–8.50]). Six studies explored differences in PTSD scores between delirious and non-delirious patients. Of the four studies initially reporting median values, two were excluded following skewness assessment for non-normal data distribution. The data from the remaining two studies were transformed into mean ± SD format for subsequent analysis. A meta-analysis of these four trials revealed that patients with delirium scored significantly higher on PTSD symptoms than those without (SMD = 0.50, 95% CI: 0.22–0.78, Z = 3.459, P<0.001).ConclusionThis meta-analysis found a significant association between PTSD and delirium.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251031880, identifier CRD420251031880.